Exploration of ethnomathematics in Riau Malay Songket - Zuhdi, Nurul Huda; Reflina, Reflina (International Journal of Trends in Mathematics Education Research, 2024)
This research is a qualitative study using an ethnographic method, aiming to identify the mathematical concepts embedded in the Riau Malay Songket motifs. The study was conducted at Dekranasda Riau Province, located at Jalan Sisingamangaraja No. 140, Pekanbaru City, Riau Province. The subject of the study is a weaver working at Dekranasda Riau Province. The research instruments are divided into two categories: the main instrument and the auxiliary instruments. The main instrument used is the interview guideline, while the auxiliary instruments include observation sheets and field documentation sheets. The data analysis techniques employed in this study are data reduction, data presentation, and drawing conclusions. The results of this study reveal mathematical concepts within the traditional Riau Songket motifs, including shapes such as triangles, ribs, circles, tubes, angular shapes, parallel lines, dots, reflections, dilations, and number patterns. This demonstrates that mathematics is inherent and develops within certain societal activities, which is referred to as ethnomathematics.